(untitled) (Damascus University Journal of agriculture sciences, 2021)
The effect of different percentages of olive mill wastewater OMWW on the some soil fertility properties, phenolic compounds and biosphere was carried out in Administration of Natural Resources Research within plastic pots in 2017 where the soil was taken from the Faculty of Agriculture - University of Damascus. The experimental design was Randomize Design, with four replicates and the treatments were: control, OMWW( 100-200- 300-400) m3/ha. Soil and OMWW were analyzed before planting. Fertility, bacterial and fungal cell counts and the measurement of phenolic compounds in the soil were analyzed after harvesting. The results showed increasing in soil salinity by increasing the concentration of OMWW. Soil mineral nitrogen, Available soil phosphorus and potassium increased in treatment that amended by 100 m3/ha of OMWW(21.57-66.12-851.3 mg/kg respectively), while. Decreased in soil by adding high concentration of OMWW. The soil content of the phenolic compounds increased significantly by adding OMWW compared to the control. In addition, the number of bacteria in the soil increased in the treatment that amended with 200 m3/ha OMWW compared to the rest of the treatments, while the number of soil bacteria deceased in treatment that amended with 400 m3/ha of OMWW. Also, the number of soil fungi increased in treatment that amended with 200 m3/ha OMWW and decreased significantly when OMWW was more concentrated than this level. Furthermore, plant and spike length was significantly increased in the treatment that amended with 100 m3/ha of OMWW as compared to all treatments. The wheat productivity increased significantly in treatment that amended with 100 m3/ha of OMWW by 12.3% compared to the control.